The use of the Regional Operational Programme of Kujawsko-Pomorskie Voivodeship funds for the development of tourism - Smoleńska, Olga; Adamiak, Czesław; Rudnicki, Roman (Journal of Education, Health and Sport, 2017)
The article presents an analysis of the use of Regional Operational Program for Kujawsko-Pomorskie Voivodeship 2007-2013 funds for the the development of tourism, with particular Focus on cultural tourism. Firstly, a spatial analysis of the use of ROP funds for the development of tourism in the voivodship was presented. Afterwards, nine concrete examples of such use of ROP funds for the development of cultural tourism were described.